Environmental impacts of food waste in Europe. (July 2018) - Scherhaufer, Silvia; Moates, Graham; Hartikainen, Hanna; Waldron, Keith; Obersteiner, Gudrun
Highlights: Impacts of food waste in relation to the total utilized food are illustrated. Results show that 186 Mt CO2 -eq, can be attributed to food waste in Europe annually. This is 15% of the impacts from the entire food supply chain. Most of the impacts originate from up-stream supply chain processes. Around 6% of the food waste related impacts result from food waste management. Abstract: Approximately 88 Million tonnes (Mt) of food is wasted in the European Union each year and the environmental impacts of these losses throughout the food supply chain are widely recognised. This study illustrates the impacts of food waste in relation to the total food utilised, including the impact from food waste management based on available data at the European level. The impacts are calculated for the Global Warming Potential, the Acidification Potential and the Eutrophication Potential using a bottom-up approach using more than 134 existing LCA studies on nine representative products (apple, tomato, potato, bread, milk, beef, pork, chicken, white fish). Results show that 186 Mt CO2 -eq, 1.7 Mt SO2 -eq. and 0.7 Mt PO4 -eq can be attributed to food waste in Europe. This is 15 to 16% of the total impact of the entire food supply chain. In general, the study confirmed that most of the environmental impacts are derived from the primary production step of the chain. That is why animal-containing food shows most of the food waste related impacts when it is extrapolated to total food waste even if cereals are higher in mass. Nearly three quarters of all food waste-related impacts for Global Warming originate from greenhouse gas emissions during the production step. Emissions by food processing activities contribute 6%, retail and distribution 7%, food consumption, 8% and food disposal, 6% to food waste related impacts. Even though the results are subject to certain data and scenario uncertainties, the study serves as a baseline assessment, based on current food waste data, and can be expanded as more knowledge on the type and amount of food waste becomes available. Nevertheless, the importance of food waste prevention is underlined by the results of this study, as most of the impacts originate from the production step. Through food waste prevention, those impacts can be avoided as less food needs to be produced.